Distraction Techniques: Telling Stories to Decrease Pain for Preschool Children During Infusion - Lina Dewi Anggraeni; Widiyanti Widiyanti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2019)
Hospital procedures, such as infusions, are often associated with pain. Preschool-aged children who are hospitalized for infusions will often exhibit a strong fearful response because their concept of body integrity has not fully developed. One way to reduce the fear of infusion pain is by using stories as a distraction technique. The purpose of this study was to identify differences in the scale of pain between members of an intervention group, to which the distraction technique was applied, and a control group, to which it was not applied. The study used quasi-experimental methods, with intervention and control groups. The study was conducted on 46 preschool aged respondents (3–6 years old), divided into a 34 member intervention group and a 12 member control group and ran from September to December 2017 in one of the private hospitals in the East Bekasi. The research employed a questionnaire to collect demographic data and used the Wong-Baker Faces Pain Scale to assess pain levels. The data analysis technique used was the independent t-test. The results showed there was a difference of pain response between the intervention and control groups with P value < 0.05. Pediatric nurses are advised to use storytelling therapy as an option for providing atraumatic care intervention. Abstrak Teknik Distraksi: Bercerita Menurunkan Nyeri Pada Anak Usia Pra Sekolah Selama Penggunaan Infus. Rasa sakit seringkali dikaitkan dengan salah satu prosedur rumah sakit yakni pemasangan infus. Reaksi anak prasekolah yang dipasang infus menunjukkan ketakutan yang luar biasa, hal itu disebabkan karena konsep integritas tubuhnya belum berkembang dengan baik. Salah satu cara untuk mengurangi ketakutan akibat nyeri pemasangan infus pada prasekolah adalah teknik distraksi bercerita. Tujuan penelitian ini untuk mengidentifikasi perbedaan skala nyeri antara kelompok intervensi dan kelompok kontrol. Penelitian ini merupakan penelitian kuantitatif dengan metode quasy eksperimen, yang menggunakan kelompok intervensi dan kelompok kontrol. Penelitian dilakukan terhadap 46 responden usia prasekolah (3-6 tahun) yang terdiri dari 34 kelompok intervensi dan 12 kelompok kontrol dari bulan September-Desember 2017 di salah satu Rumah Sakit Swasta di wilayah Bekasi Timur. Instrumen penelitian menggunakan kuisioner data demografi dan lembar observasi skala nyeri Wong Baker Faces Pain. Teknik analisis data menggunakan Uji Independent T test.Hasil penelitian menunjukkan terdapat perbedaan respon nyeri antara kelompok intervensi dan kelompok kontrol dengan nilai p = 0,012 (< 0.05). Perawat anak sebaiknya menggunakan metode bercerita sebagai sarana asuhan keperawatan atraumatik. Kata kunci: cerita, nyeri, pemasangan infus, prasekolah, teknik distraksi